2012
DOI: 10.3732/ajb.1100198
|View full text |Cite
|
Sign up to set email alerts
|

Herbarium specimens, photographs, and field observations show Philadelphia area plants are responding to climate change

Abstract: Of the species studied, woody plants with short flowering duration are the best indicators of a warming climate. For monthly minimum temperatures, temperatures 1 or 2 mo prior to flowering are most significantly correlated with flowering time. Studies combining herbarium specimens, photographs, and field observations are an effective method for detecting the effects of climate change on flowering times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
140
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(151 citation statements)
references
References 31 publications
8
140
1
Order By: Relevance
“…The effect sizes seen in annual average warming on phenology (−2.27 d/°C) and fall warming on phenology (2.54 d/°C) are similar to effect sizes seen in similar studies (10,48), although some studies have shown considerably greater effect sizes (11). Flowering time of Rhododendron spp.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…The effect sizes seen in annual average warming on phenology (−2.27 d/°C) and fall warming on phenology (2.54 d/°C) are similar to effect sizes seen in similar studies (10,48), although some studies have shown considerably greater effect sizes (11). Flowering time of Rhododendron spp.…”
Section: Discussionsupporting
confidence: 47%
“…These have increasingly shown that not only can the "messy" data from herbarium collections be used to infer phenology, but that these data can reveal the complex effects on phenology of geography (43), pollination (62), morphological traits (48,52), and, in this study, the contrasting response of warming across different seasons. By drawing together historical collections dispersed across many herbaria, we show that herbarium records have the ability to provide information beyond systematics, and further afield than eastern North America and Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lal et al [23] have argued that date of onset of summer monsoon over India could become more variable in future owing to climate change. Under these conditions, it might be difficult for dispersal phenologies tied to monsoons to track an increasingly variable climate [24,25]. A recent study, for example, has shown that long-established phenologies can be disrupted by climate change [26].…”
Section: Discussionmentioning
confidence: 99%
“…The sites were visited every 3-4 days in all 3 years. In 2013, monitoring was qualitative and subjective, following an approach successfully used by Panchen et al (2012), wherein the date of first flower, peak flowering and finish of flowering of each population was recorded. After reviewing the 2013 results, the approach for subsequent years was changed to counting flowers to provide a more definitive date for start, peak and finish of flowering.…”
Section: Methodsmentioning
confidence: 99%